Exploring the Relationship between Organizational Culture and Well-Being of Educational Institutions in Jordan - Dina Ahmad Alkhodary (Administrative Sciences, 2023)
Organizational culture is a critical factor in shaping companies’ overall well-being, which can impact their employees’ job satisfaction, loyalty, creativity, and productivity. In this study, the researchers aimed to examine the relationship between organizational culture and companies’ well-being in the Education sector in Jordan. To achieve their goal, the researchers surveyed 500 participants from various departments in the Education sector in Jordan, categorizing organizational culture into four types: Clan, Adhocracy, Market, and Hierarchy. The well-being of companies was measured through employee loyalty, creativity, and productivity. The data from 352 valid questionnaires were analyzed using SPSS. This study’s findings suggest that a positive organizational culture is significantly associated with increased employee job satisfaction, loyalty, creativity, and productivity. Moreover, the study highlighted the importance of developing a positive organizational culture, fostering a sense of community and shared values, providing opportunities for employee development and growth, and promoting a supportive and inclusive work environment to achieve organizational success. Understanding the role of organizational culture in promoting employee well-being and companies’ success is critical, particularly in the Education sector in Jordan. This study’s recommendations provide valuable insights for companies to prioritize developing a positive organizational culture to achieve long-term success and employee well-being.